Health system challenges affecting HIV and tuberculosis integration at primary healthcare clinics in Durban, South Africa - Dishiki Kalonji; Ozayr H. Mahomed (AOSIS, 2019)
Background: Tuberculosis (TB) is the most common presenting illness among people living with human immunodeficiency virus (HIV), with co-infection occurring in up to 60% of cases in South Africa. In line with international guidelines, South Africa has adopted an integrated model at primary healthcare level to provide HIV and TB services by the same healthcare provider at the same visit. Aim: The aim of the study was to conduct a rapid appraisal of integration of HIV and TB services at primary healthcare level in eThekwini District in 2015. Setting: The study was conducted in 10 provincial primary healthcare clinics in the eThekwini Metropolitan Health District in KwaZulu-Natal Province. Methods: An observational, cross-sectional study was conducted. Key informant interviews with operational managers and community health workers were conducted, as well as a review of registers and electronic databases for the period of January to March 2015. Results: Two clinics complied with the mandated integrated model. Three clinics were partially integrated; while five clinics maintained the stand-alone model. Possible constraints included reorganisation of on-site location of services, drug provision, TB infection control and inadequate capacity building, while potential enablers comprised structural infrastructure, staffing ratios and stakeholder engagement. Conclusion: HIV and TB integration is suboptimal and will need to be improved by addressing the systemic challenges affecting health service delivery, including strengthening supervision, training and the implementation of a change management programme.